Isle Royale National Park - Kalbacken, Joan (New York Children's Press, 1996)
Describes the history, landscape, and wildlife of the oldest, largest, and only island national park in the United States
Includes bibliographical references (p. 44) and index
Hurg
5
Keywords: National parks and reserves; Natural history -- Michigan -- Isle Royale National Park; Isle Royale National Park